How interacting constraints shape emergent decision-making of national-level football referees - Russell, S.; Renshaw, I.; Davids, K. (Qualitative Research in Sport, Exercise and Health, 2019)
Here, using a grounded theory methodology, we explored the experiential knowledge of nine national-level Association Football referees (aged 23-35 yrs; 3.8 yrs mean minimum national-level experience) with the aim of better understanding why referees make decisions during performance. Results indicated that referee decision-making actions were not predominantly aimed at traditional notions of decision-making accuracy (e.g. correctly identifying rule transgressions), but were instead focussed on meeting two overarching task goals: maintaining control and preserving the integrity of the competitive game. These objectives were, in part, informed by co-invested task outcomes, which referees perceived that players, spectators, coaches and fellow referees had about `how the game should be played`. Analysis revealed four decision-making priorities (`four pillars`) used to meet these expectations; these were conceptual notions of: safety, fairness, accuracy and entertainment. We discuss how these results provide a case that: (i) referees co-construct the game with players and (ii) referee decision-making is an emergent process of the performer-environment relationship nested within task goals. Finally, we recommend that future research investigate decision-making accuracy within the context of a competitive match and that distinctions be made between types of bias and the complex strategies referees use to manage the game.